Analysis of Online Customer Reviews, Influencer Endorsements, and Price Perceptions on Purchasing Decisions for Eiger Products in the Sumut Indonesia Climbing Community - Ajie Dwi Tandayu; Ari Prabowo; Aisyah Azhar Adam (International Forum of Researchers and Lecturers, 2024)
Purchase Decision is a decision to buy a product or brand you like, but two factors can arise between purchase intention and purchase decision. This research aims to determine the influence of online customer reviews, influencer endorsements and price perceptions on purchasing decisions. The type of research used in this research is quantitative research. In determining the research sample, the Slovin formula was used, where the number of samples obtained was 100 samples. Data was collected using a questionnaire that had been tested for validity and reliability and processed using SPPSS 26. Based on the partial test, the Online Customer Review variable had a positive and significant effect on the decision to purchase Eiger products in the Indonesian North Sumatra Climber Community. A value of t-count of 8.139 > 1.66 t-table was obtained, then the Endorsement Influencer variable had a positive and significant influence on Purchasing Decisions, a value of t-count of 2.169 > 1.66 t-table was obtained, and the Price Perception variable had a positive and significant influence on Purchase Decisions with a t-count value of 3.885 > 1.66 t-table . Simultaneous test results show that the online customer review (X1), influencer endorsement (X2) and price perception variables (X3) together have a positive and significant effect on the decision to purchase Eiger products in the Indonesian North Sumatra climbing community.